Menggunakan Metode Permainan Dalam Upaya Meningkatkan Motivasi Dan Hasil Belajar Matematika Di Kelas VI A SD Integral Al Amiin Hidayatullah Timika Tahun Pelajaran 2018/2019 - Ramlah Ramlah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Mathematics learning is a reciprocal interaction between students and teachers and between students and students which involves various components to achieve mathematics learning goals. Mathematics learning in schools continues to be pursued in order to increase motivation, quality of results and student learning outcomes. Various methods continue to be used, one of which is by synergizing the components involved in learning. The components involved in learning are objectives, learning materials (materials), learning activities, methods, media, tools and resources as well as evaluation.